2021
DOI: 10.1139/apnm-2021-0190
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wearing a surgical and cloth mask during cycle exercise

Abstract: We sought to determine the impact of wearing cloth or surgical masks on the cardiopulmonary responses to moderate-intensity exercise. Twelve subjects (n=5 females) completed three, 8-min cycling trials while breathing through a: non-rebreathing valve (laboratory control), cloth, or surgical mask. Heart rate (HR), oxyhemoglobin saturation (SpO2), breathing frequency (Fb), mouth pressure, partial pressure of end-tidal carbon dioxide (PetCO2) and oxygen (PetO2), dyspnea, were measured throughout exercise. A subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 36 publications
1
42
1
2
Order By: Relevance
“…This lower blood oxygen saturation would be expected due to increased partial pressure of CO 2 at high exercise intensity, increased tidal volume, and an inadequate oxygen and carbon dioxide exchange due re-breathing enriching inhaled air with CO 2 [8]. Contrary to our results, authors did not find a blood oxygen saturation decrease with surgical masks, either during extenuated [33], vigorous [11] or steady exercise [34]. However, a key factor explaining the differences lies in the intensity and level of previous training.…”
Section: Discussioncontrasting
confidence: 99%
“…This lower blood oxygen saturation would be expected due to increased partial pressure of CO 2 at high exercise intensity, increased tidal volume, and an inadequate oxygen and carbon dioxide exchange due re-breathing enriching inhaled air with CO 2 [8]. Contrary to our results, authors did not find a blood oxygen saturation decrease with surgical masks, either during extenuated [33], vigorous [11] or steady exercise [34]. However, a key factor explaining the differences lies in the intensity and level of previous training.…”
Section: Discussioncontrasting
confidence: 99%
“…They found that HR, respiratory rate, blood pressure, and time to exhaustion did not differ between groups. Doherty et al (2021) examined the impact of wearing cloth or surgical masks on the cardiopulmonary responses in 12 healthy young individuals during an 8-min moderate-intensity cycling exercise. It was found that wearing surgical or cloth masks during exercise had no impact on breathing frequency, tidal volume, oxygenation, and heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…Since the outbreak of COVID-19, several primary studies (Fikenzer et al, 2020;Lassing et al, 2020;Shaw et al, 2020;Doherty et al, 2021;Driver et al, 2021;Epstein et al, 2021) have been conducted and attempted to evaluate the impact of face masks on human physiological and perceptual responses during exercise. While some studies revealed that wearing face mask would pose negative impact on performance and physiological variables (Fikenzer et al, 2020;Lassing et al, 2020;Driver et al, 2021), others demonstrated contrasting results (Shaw et al, 2020;Doherty et al, 2021;Epstein et al, 2021). These disparate findings between studies might be attributed to the notable methodological differences in relevant literature.…”
Section: Introductionmentioning
confidence: 99%
“…In total, significant changes (p<0.05) could be found in most of the evaluated studies that measured body CO 2 content during mask use [18,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] (Table 2). Experiments with relatively short evaluation times [45] or questionable study design [46,47] showed no effects caused by masks. However, some well conducted studies also found no statistical difference between mask and no mask use, though measured CO 2 levels were continuously higher in mask wearers [25,48].…”
Section: Effects Of Masks On Carbon Dioxide Re-breathingmentioning
confidence: 95%